Microbiological and real-time mechanical analysis of Bacillus licheniformis and Pseudomonas fluorescens dual-species biofilm. Issue 7 (30th May 2019) - Abriat, Clemence; Virgilio, Nick; Heuzey, Marie-Claude; Daigle, France
Abstract : In natural habitats, bacterial species often coexist in biofilms. They interact in synergetic or antagonistic ways and their interactions can influence the biofilm development and properties. Still, very little is known about how the coexistence of multiple organisms impact the multispecies biofilm properties. In this study, we examined the behaviour of a dual-species biofilm at the air–liquid interface composed by two environmental bacteria: Bacillus licheniformis and a phenazine mutant of Pseudomonas fluorescens . Study of the planktonic and biofilm growths for each species revealed that P. fluorescens grew faster than B. licheniformis and no bactericidal effect from P. fluorescens was detected, suggesting that the growth kinetics could be the main factor in the dual-species biofilm composition. To validate this hypothesis, the single- and dual-species biofilm were characterized by biomass quantification, microscopy and rheology. Bacterial counts and microscale architecture analysis showed that both bacterial populations coexist in the mature pellicle, with a dominance of P. fluorescens . Real-time measurement of the dual-species biofilms' viscoelastic (i.e. mechanical) properties using interfacial rheology confirmed that P. fluorescens was the main contributor of the biofilm properties. Evaluation of the dual-species pellicle viscoelasticity at longer time revealed that the biofilm, after reaching a first equilibrium, created a stronger and more cohesive network. Interfacial rheology proves to be a unique quantitative technique, which combined with microscale imaging, contributes to the understanding of the time-dependent properties within a polymicrobial community at various stages of biofilm development. This work demonstrates the importance of growth kinetics in the bacteria competition for the interface in a model dual-species biofilm.